ROLE OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN INDIAN ECONOMY - Nath, Hemanta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Micro, Small and Medium Enterprises (MSMEs) sector has been recognized as engine of growth all over the world. To foster economic development, generation of jobs, reduction in poverty and promotion of equality, the role of micro, small and medium enterprises (MSMEs) becomes crucial in every economy of the world. The MSME sector encourages equitable distribution and inclusive growth as an engine of economic progress. MSMEs have the highest employment growth rate, which has a positive impact on export and industrial growth. The primary objective of this article is to analyse MSMEs performance and their contribution to Indian economy.